The Food Supply Challenges of Remote Siberian Forts: A Case Study of Lensky Fort in the Seventeenth Century - Kalashnikova, Angelina (Food & History, 2025)
Abstract This article examines dietary challenges and adaptations in the development of Siberian settlements during Russian colonization, focusing on Lensky Fort (future Yakutsk). Food provision posed significant difficulties for Siberian cities and forts, including Lensky. Military personnel often went years without salaries or essential supplies like grain and salt. Vulnerable groups, such as fur tribute collectors on expeditions and servicemen travelling between settlements, faced acute food shortages, often more severe than those stationed in forts. Due to scarce grain supplies, cultivating arable crops became the primary strategy for addressing shortages. Siberian authorities promoted farming by offering loans and equipment, aiming for supply independence. Despite these efforts, arable farming failed to meet demand. Although the peasant population grew slowly, Yakutsk remained reliant on grain imports from Western Siberia through the seventeenth century. In this context, newcomers, including servicemen, hunters, and traders, adapted to local diets when grain was unavailable, incorporating indigenous food sources. Abstract Cet article examine comment les établissements sibériens se sont adaptés aux défis alimentaires lors de la colonisation russe, en se concentrant sur le fort Lensky (futur Yakoutsk). L’approvisionnement en nourriture était un problème crucial : le personnel militaire passait des années sans salaire ni provisions essentielles comme le grain et le sel, tandis que les collecteurs de tributs en fourrures et les serviteurs en déplacement souffraient de graves pénuries alimentaires. Face à la rareté du grain importé, la culture céréalière locale est devenue une nécessité. Les autorités sibériennes ont tenté d’atteindre l’autosuffisance alimentaire en offrant des prêts et du matériel agricole, mais leurs efforts n’ont pas suffi. Bien que la population paysanne ait lentement augmenté, Yakoutsk est resté dépendant des approvisionnements en grain de Sibérie occidentale. En l’absence de grain, les nouveaux arrivants – serviteurs, chasseurs, commerçants – s’adaptaient en utilisant les ressources alimentaires locales pour subvenir à leurs besoins.
Keywords: faim